2010
DOI: 10.14723/tmrsj.35.857
|View full text |Cite
|
Sign up to set email alerts
|

Clouding Properties of Maleic Acid/Acrylamide Gels

Abstract: Clouding-feature observations were made for several maleic acid/acrylamide (MA/AAm) gels with different fractions of MA and cross-linker concentrations for the first time. In the investigations, both of the conditions were found to considerably influence the turbidity of the MA/AAm gels. In addition, it was also found that turbidity of some MA/AAm gels changes with temperature, which indicates the inhomogeneity alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the previous paper, the authors reported that the AAm/MA gels show opaqueness in a range of BIS concentrations and temperatures for the first time [4], however, in the investigations, only a few specimens were observed and the opaqueness was observed only by their appearance. On the other hand, in the present study, the authors have carried out quantitative investigations by measuring turbidity of much more specimens; and, in addition, the SAXS measurements have been carried out in order to examine the correlation between the turbidity and nano-scale structure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the previous paper, the authors reported that the AAm/MA gels show opaqueness in a range of BIS concentrations and temperatures for the first time [4], however, in the investigations, only a few specimens were observed and the opaqueness was observed only by their appearance. On the other hand, in the present study, the authors have carried out quantitative investigations by measuring turbidity of much more specimens; and, in addition, the SAXS measurements have been carried out in order to examine the correlation between the turbidity and nano-scale structure.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the authors once adopted maleic acid (MA), a dicarboxylic acid, as an ionizing ingredient aiming at promotion of the capturing efficiency. However, in some experimental conditions, a copolymer hydrogel containing MA (acrylamide/ maleic acid [AAm/ MA] gel) was observed to show turbidity [4] indicating emergence of an inhomogeneity which can be undesirable for the heavymetal-ion capturing functionality. Therefore, detailed investigations on the conditions for occurrence of the turbidity seem to be important for developing the new heavy-metal capturing hydrogels.…”
Section: Introductionmentioning
confidence: 99%